2002
DOI: 10.1046/j.1469-1809.2002.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of probability distribution of diplotype configuration (diplotype distribution) for each subject from genotypic data using the EM algorithm

Abstract: Haplotype analysis is important for mapping traits. Recently, methods for estimating haplotype frequencies from genotypes of unrelated individuals based on the expectation-maximization (EM) algorithm have been developed. Our program estimates haplotype frequencies in the population and determines the posterior probability distribution of diplotype configuration (diplotype distribution) for each subject based on the estimated haplotype frequencies. Samples from three ethnic groups for the smoothelin gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 12 publications
1
59
0
Order By: Relevance
“…(29) In the present study, homozygosity for the reference allele at the CBR1c.627C>T and +967G>A loci was observed to be associated with increased clearance and reduced exposure levels of doxorubicin in Asian breast cancer patients. The reasons for the lack of influence of the homozygous variant alleles at the CBR1 c.627C>T and +967G>A loci on doxorubicin pharmacokinetic parameters are unknown and could possibly be due to a smaller cohort of breast cancer patients studied.…”
Section: Discussionmentioning
confidence: 85%
“…(29) In the present study, homozygosity for the reference allele at the CBR1c.627C>T and +967G>A loci was observed to be associated with increased clearance and reduced exposure levels of doxorubicin in Asian breast cancer patients. The reasons for the lack of influence of the homozygous variant alleles at the CBR1 c.627C>T and +967G>A loci on doxorubicin pharmacokinetic parameters are unknown and could possibly be due to a smaller cohort of breast cancer patients studied.…”
Section: Discussionmentioning
confidence: 85%
“…We applied the genotypic data to the LDSUPPORT program 25 to estimate the haplotype frequencies in the population and to calculate the posterior probability of diplotype distribution for each subject. This program was designed for typing of haplotype using a maximum likelihood estimation method which is based on the expectation maximization (EM) algorithm assuming Hardy-Weinberg's equilibrium for the population.…”
Section: Typing Of Haplotype and Diplotype Configurationsmentioning
confidence: 99%
“…Some haplotypes were unambiguously identified from subjects with homozygous variations at all sites or a heterozygous variation at only one site. Diplotype configurations were inferred by LDSUPPORT software, which determines the posterior probability distribution of the diplotype for each subject based on the estimated haplotype frequencies (Kitamura et al 2002). Although the nomenclature for nonsynonymous DPYD alleles (DPYD*1 to DPYD*13) have been already publicized CollieDuguid et al 2000;Johnson et al 2002), several reported alleles remain unassigned.…”
Section: Pcr Conditions For Dna Sequencingmentioning
confidence: 99%